Crozier’s paradox and kin recognition: insights from simplified models - Scott, T (Elsevier, 2024)
Crozier’s paradox suggests that genetic kin recognition will not be evolutionarily stable. The problem is that more common tags (markers) are more likely to be recognised and helped. This causes common tags to increase in frequency, eliminating the genetic variability that is required for genetic kin recognition. In recent years, theoretical models have resolved Crozier’s paradox in different ways, but they are based on very complicated multi-locus population genetics. Consequently, it is hard to see exactly what is going on, and whether different theoretical resolutions of Crozier’s paradox lead to different types of kin discrimination. I address this by making unrealistic simplifying assumptions to produce a more tractable and understandable model of Crozier’s paradox. I use this to interpret a more complex multi-locus population genetic model where I have not made the same simplifying assumptions. I explain how Crozier’s paradox can be resolved, and show that only one known theoretical resolution of Crozier’s paradox – multiple social encounters – leads without restrictive assumptions to the type of highly cooperative and reliable form of kin discrimination that we observe in nature. More generally, I show how adopting a methodological approach where complex models are compared with simplified ones can lead to greater understanding and accessibility.